Allergic contact dermatitis in psoriasis. (4th February 2019) - Claßen, A.; Buhl, T.; Schubert, S.; Worm, M.; Bauer, A.; Geier, J.; Molin, S.; ,
Abstract : Linked Article:  Claßen et al. Br J Dermatol 2019;180 :315–320